Designing The Concepts - Framework & The Maturity Level Of Smart Pondok Pesantren (Islamic Boarding Schools) - Sendi Novianto; Indra Gamayanto; Farrikh Alzami (Journal of Applied Intelligent System, 2021)
Abstract - The development of information technology and significant progress is happening today, where changes need to face increasingly high global competition. Islamic boarding schools are the centre of change, where boarding schools must develop four important factors: human resource development, information technology, culture and e-spirituality. This article is about developing smart city 3.0 and 5.0, where the resulting framework and methods can apply to Islamic boarding schools. Our research object is Islamic boarding schools, and in this place, we do community service. This article's results are the framework and the maturity level of smart Islamic boarding schools, where there are three indicators (people-culture, technology-business, implementation-global goals)  and three important levels (stage 1-the foundation, stage 2-good foundation, stage 3- great foundation), which are the basis for developing a smart islamic boarding school. Moreover, this article is version 1.0, which in its development will extend to the application. An application Si-PenO (Online registration information system) completed at the Askhabul Kahfi Islamic boarding school as proof of applying the concept we created in this article. This change is needed to face globalization, and change is a good thing if it does systematically. Furthermore, this article will continue to develop in versions 2.0 and 3.0 and applications that we will implement in Islamic boarding schools.